Management of Stage III Non–Small-Cell Lung Cancer: ASCO Guideline. Issue 12 (20th April 2022) - Daly, Megan E.; Singh, Navneet; Ismaila, Nofisat; Antonoff, Mara B.; Arenberg, Douglas A.; Bradley, Jeffrey; David, Elizabeth; Detterbeck, Frank; Früh, Martin; Gubens, Matthew A.; Moore, Amy C.; Padda, Sukhmani K.; et al.
Abstract : PURPOSE: To provide evidence-based recommendations to practicing clinicians on management of patients with stage III non–small-cell lung cancer (NSCLC). METHODS: An Expert Panel of medical oncology, thoracic surgery, radiation oncology, pulmonary oncology, community oncology, research methodology, and advocacy experts was convened to conduct a literature search, which included systematic reviews, meta-analyses, and randomized controlled trials published from 1990 through 2021. Outcomes of interest included survival, disease-free or recurrence-free survival, and quality of life. Expert Panel members used available evidence and informal consensus to develop evidence-based guideline recommendations. RESULTS: The literature search identified 127 relevant studies to inform the evidence base for this guideline. RECOMMENDATIONS: Evidence-based recommendations were developed to address evaluation and staging workup of patients with suspected stage III NSCLC, surgical management, neoadjuvant and adjuvant approaches, and management of patients with unresectable stage III NSCLC. Additional information is available at www.asco.org/thoracic-cancer-guidelines .